(3GdRjGOGJ aj cJGH GdeDJda hGdeNJdas - (3CHhGdYHGS LYaQ Hf eMeO Hf GdoeYJR GdoeSJZaQjs; (3CHh eMeO GdGROj , YHO GdZfj Hf SYjO, CHh eMeO,J (B409 (3g` s ((3jhSa Hf CHj BOe Hf BHj YHOGddg GdeQGZj GdOeTbj s)
(3ChdgG (B:s
(3CNHQfG CHheSde YeQ Hf Ydj GddjKj GdoHNGQj , bGd(B: (3SeYJ GdTjN GdMGaX CHG eMeO GdMSf Hf CMeO GdSeQbfOj HfjSGHhQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B45 - (3U(B67s
(3HgG SeGYs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs